How do public investments in gender equality initiatives and publication patterns interrelate? The case of Germany. (April 2020) - Bührer, Susanne; Frietsch, Rainer
Highlights: The German research system by a low participation of female researchers. Two large policy initiatives were launched to overcome this situation. The role of female scientists in the publication landscape changed significantly. It underlines the scientific benefits that emerge from improved gender equality. Abstract: This article examines whether two of the major German flagship programmes to increase the participation of female researchers in the German science system, the "Women Professorship Programme" and the "Pact for Research and Innovation", have actually increased the number of women, especially in leadership positions. In a second step, we analyse whether such an assumed increase influences the publication patterns of authors with German affiliation. This article is based on literature and desk research as well as bibliometric analysis using Scopus. The most important result is that the number of women in research has indeed increased significantly in recent years and that, accordingly, more women are the (co)authors of scientific publications. In particular, it can be seen that quality indicators such as citations and excellence rates are high for female authors. This enables us to show that more women in the science system not only bring about a "gain in justice", but also a concrete scientific benefit.